2014
DOI: 10.1007/s00520-014-2482-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydronephrosis in patients with cervical cancer: an assessment of morbidity and survival

Abstract: Purpose Hydronephrosis is a frequently observed but understudied complication in patients with cervical cancer. To better characterize hydronephrosis in cervical cancer patients, the current study sought (1) to describe hydronephrosis-associated morbidity and (2) to analyze the prognostic effect of hydronephrosis in patients with a broad range of cancer stages over time. Methods The Mayo Clinic Tumor Registry was interrogated for all invasive cervical cancer patients seen at the Mayo Clinic from 2008 through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 10 publications
3
41
0
2
Order By: Relevance
“…Obstructive uropathy is encountered in 14 to 44 percent of the cases with cervical cancer, and is a common cause of cervical cancer related mortality (Chao et al 1998;Rose et al, 2010;Wit and Horenbas, 2014;Patel et al, 2015). Besides medical treatment, percutaneous nephrostomy and ureteral stent placement is commonly undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive uropathy is encountered in 14 to 44 percent of the cases with cervical cancer, and is a common cause of cervical cancer related mortality (Chao et al 1998;Rose et al, 2010;Wit and Horenbas, 2014;Patel et al, 2015). Besides medical treatment, percutaneous nephrostomy and ureteral stent placement is commonly undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…Symptoms are most often absent, as hydronephrosis has a progressive onset and the contralateral kidney may assure adequate function, leading to a delayed diagnosis. 9,10 In this study, hydronephrosis was seen in the postoperative period in both cervical and vaginal cancer patients, with a significantly higher incidence in the second group (43.8%).…”
Section: Discussionmentioning
confidence: 51%
“…7,8 Several studies have shown, in the case of patients undergoing modified radical hysterectomy with pelvic lymphadenectomy, especially for cervical cancer, that hydronephrosis is not an uncommon late complication, with significant impact not only on quality of life, but also on survival. 9,10 Scarce data are available in the literature regarding the incidence and impact on survival of postoperative hydronephrosis in vaginal cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…The most common sites of such metastasis are the lungs, bones, aorta, and celiac and supraclavicular lymph nodes, whereas, kidney metastasis is rare (34). A very common complication of advanced cervical cancer is obstructive nephropathy which one of the best techniques for resolving the obstruction could be ultrasonography-guided percutaneous neph rostomy (PCN) (35). In fact, PCN can recover renal function of more than 60% of cervical cancer patients, resulting in preventing renal replacement therapy in these patients (36).…”
Section: Cervical Cancer and Kidneymentioning
confidence: 99%
“…In fact, PCN can recover renal function of more than 60% of cervical cancer patients, resulting in preventing renal replacement therapy in these patients (36). In addition, cervical cancer patients may develop hydronephrosis, as a cancer-related or cancer treatmentrelated complication, which is associated with higher morbidity and worse survival (35).…”
Section: Cervical Cancer and Kidneymentioning
confidence: 99%